THE EFFECT OF STRATEGIC PLANNING AND BUDGETING AND RESOURCES BASED VIEW ON ORGANIZATIONAL PERFORMANCE MEDIATED BY ORGANIZATIONAL COMMITMENT ON THE TITLE OF TNI AD UNITS IN LAND BORDER AREAS - Budi Prijono; Kusnadi Kusnadi; Willy Arafah; Boris Lukman (Journal of Economics, Management, Entrepreneurship, and Business (JEMEB), 2021)
The purpose of this study was to examine the Effect of Strategic Planning and Budgeting and Resources Based View on Organizational Performance Mediated by Organizational Commitments on Army Unit Title in Land Border Areas. The methodology used in this study is hypothetical testing causality using cross sectional, hypothesis testing is a method of decision making that is based on data analysis of controlled and uncontrolled experiments on the Army Unit Title in the Border Area. The population numbered 465 people with a sample of 160 respondents. Data collection using questionnaires and data analysis techniques using Path Analysis and PLS. The model proposed in this study shows the direct and indirect effects of Strategic Planning and Budgeting and Resources Based View on Organizational Performance Mediated by Organizational Commitment. Future research must study other variables that influence the influence of Organizational Performance such as job satisfaction, leadership style and organizational culture. This research shows that Strategic Planning and Budgeting and Resources Based View and Organizational Commitment affect Organizational Performance both directly and indirectly. This research is a useful tool to improve Organizational Performance through enhancing Strategic Planning and Budgeting and Resources Based View and Organizational Commitments. This research model refines the overall understanding that there are direct and indirect effects of Strategic Planning and Budgeting and Resources Based View on Organizational Performance mediated by Organizational Commitment.